A comparative analysis of the community-based care and program for the elderly in the Seychelles and Mauritius Islands - Vivienne Alexandra Sharri, Lesperance (Magyar Gerontológia, 2023)
The World Health Organization describes an elderly person as someone who is aged 60 years and older and further predicts that by 2030, the number of older people will rise by 1.4 billion (WHO, 2017). This phenomenon has not spared the Small Island Developing States (SIDS); according to the United Nations (2023), they anticipated growth from 6.5 to 14.0 million older persons between 2021 and 2050. Undoubtedly, these figures are indicative of significant growth in the aging population across the world, and this is merely the chronological age; needless to say, numerous physical, psychological, and environmental factors can impede longevity and healthy aging.